How to read ambiguity well Reading ambiguity in Luke and Acts - Davis, Kendall A. (2025)
This article offers a hermeneutical account of ambiguity using Luke and Acts as an extended case study. After discussing the difficulties in identifying purposeful ambiguity in biblical texts, verbal ambiguity is distinguished from ambiguity beyond the sentence level, such as ambiguities of plot or character. Instead of approaching ambiguity primarily as a failure of language or a problem to be solved, this article offers a framework for thinking about ambiguity as an invitation to read a text from multiple angles. The discussion is illustrated throughout with a series of examples taken from Luke and Acts. I close with reflections on how this approach to ambiguity is helpful when reading scripture against different cultural contexts and in the study of New Testament Christology.
Keywords: Acts; Christology; Luke; Ambiguity; Hermeneutics